Individets rettigheder - Khader, Naer (Kvinder, Køn & Forskning, 2000)
The article contextualizes the debate of customary laws in England into the Danish political landscape. The dilemma in the Danish debate is the lack of recognition of a much more diversified society composed of different cultural and religious groups. On the other hand it is necessary to maintain the constitution based on individual rights. The article proposes changes in the Constitution as to accept other cultural and religious minority groups.